Clinical Demographics Characteristic of Total Knee Arthroplasty at Prof IGNG Ngoerah General Hospital, Bali, Indonesia - I Gusti Ngurah Wien Aryana; Cokorda Gde Oka Dharmayuda; Febyan Febyan; Dominicus Dimitri; Shianita Limena; Leonardus William Kuswara (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Total knee arthroplasty (TKA) is a widespread surgical procedure for severe arthritis. By 2030, primary TKA would reach over 1.2 million procedures annually in the United States. In Indonesia, the prevalence of joint disease is about 19.5 million cases. This study aims to evaluate the clinical demographics characteristics of TKA in Prof. Ngoerah General Hospital, Bali, Indonesia.Subjects and Method: This is a descriptive study using a Cross-Sectional method with a total 57 adult patients undergoing TKA caused by Osteoarthritis grade III/IV in Prof IGNG Ngoerah Hospital from June 2020-June 2022. The dependent variable is the TKA procedure. Independent Variable is Age, gender, grade of knee osteoarthritis, comorbidities, and complications Data from the medical record was collected and stored in a Microsoft Office Excel 365 spreadsheet, the distributive table was analyzed and collected by using SPSS.Results: Patient characteristic is dominated by an elderly female (84.2%), with age group 61-70 (38.6%). Comorbidities in this study include hypertension (28.1%), type II diabetes (10.5%), and rheumatoid disease (1.8%). The main complication recorded in this study includes joint stiffness (3.5%), and persistent pain (5.3%).Conclusion: After Total Knee Arthroplasty was performed on 57 patients with a wide range of comorbidities, only a small number of complications occurred. This study implied that TKA could be performed even if the patient had some comorbidities as long as the patient pursued a complete pre and post-operative evaluation algorithm of the procedure.Keywords: knee arthroplasty, osteoarthritis, human and medicine, rehabilitationCorrespondence: IGN Wien Aryana, Consultant of Sports Medicine, Dept. Orthopaedic and Traumatology, Prof IGNG Ngoerah General Hospital, Faculty of Medicine, Udayana University. Jl. Diponegoro, Dauh Puri Klod. Denpasar City, Bali 80113 Email: wienaryanaortho@gmail.com. Mobile: +62811385263.Indonesian Journal of Medicine (2023), 08(02): 128-135https://doi.org/10.26911/theijmed.2023.08.02.01